Trade and employment in the global crisis - Jansen, Marion; Uexküll, Erik von.; International Labour Office; Academic Foundation (New Delhi, India); ProQuest (firma) (Geneva : International Labour Office ; New Delhi : Academic Foundation, 2010)
With reference to Developing countries.
Includes bibliographical references (p. [169]-174).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Unemployment -- Developing countries; Financial crises -- Developing countries; Recessions -- Developing countries; Developing countries -- Commerce; elektronické knihy; electronic books